Expansion of FGFR3-positive nucleus pulposus cells plays important roles in postnatal nucleus pulposus growth and regeneration - Meng Xu; Junlan Huang; Min Jin; Wanling Jiang; Fengtao Luo; Qiaoyan Tan; Ruobin Zhang; Xiaoqing Luo; Liang Kuang; Dali Zhang; Sen Liang; Huabing Qi; et al. (Stem Cell Research & Therapy, 2022)
Abstract Background Intervertebral disc degeneration (IVDD) can cause low back pain, a major public health concern. IVDD is characterized with loss of cells especially those in nucleus pulposus (NP), due to the limited proliferative potential and regenerative ability. Few studies, however, have been carried out to investigate the in vivo proliferation events of NP cells and the cellular contribution of a specific subpopulation of NP during postnatal growth or regeneration. Methods We generated FGFR3-3*Flag-IRES-GFP mice and crossed FGFR3-CreERT2 mice with Rosa26-mTmG, Rosa26-DTA and Rosa26-Confetti mice, respectively, to perform inducible genetic tracing studies. Results Expression of FGFR3 was found in the outer region of NP with co-localized expressions of proliferating markers. By fate mapping studies, FGFR3-positive (FGFR3+) NP cells were found proliferate from outer region to inner region of NP during postnatal growth. Clonal lineage tracing by Confetti mice and ablation of FGFR3·+ NP cells by DTA mice further revealed that the expansion of the FGFR3+ cells was required for the morphogenesis and homeostasis of postnatal NP. Moreover, in degeneration and regeneration model of mouse intervertebral disc, FGFR3+ NP cells underwent extensive expansion during the recovery stage. Conclusion Our present work demonstrates that FGFR3+ NP cells are novel subpopulation of postnatal NP with long-existing proliferative capacity shaping the adult NP structure and participating in the homeostasis maintenance and intrinsic repair of NP. These findings may facilitate the development of new therapeutic approaches for IVD regeneration.